Efforts of Teachers in Instilling Religious Moderation Values and Learning Christian Education - Susanto, Adri; Prihadi, Stephanus; Apandie, Chris (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mataram, 2025)
Neoliberalism, as a dominant paradigm across various sectors, has significantly impacted the practice and direction of contemporary education. This article aims to critically examine the influence of neoliberalism on education through the lens of Christian educational philosophy. The study employs a qualitative literature review method, analyzing relevant sources from economics, education, and Christian theology. The findings reveal that neoliberalism drives the commercialization of education, shifting its orientation from character formation to market-driven objectives. In contrast, Christian educational philosophy emphasizes education as a means of holistic human development grounded in Christian values. This study concludes that Christian education must actively provide an alternative to neoliberal dominance by reaffirming education's role as a faith-driven calling to serve others and glorify God.